Transcriptomic and epigenomic profiling reveals altered responses to diesel emissions in Alzheimer's disease both in vitro and in population-based data - Saveleva, Liudmila; Cervena, Tereza; Mengoni, Claudia; Sima, Michal; Krejcik, Zdenek; Vrbova, Kristyna; Sikorova, Jitka; Mussalo, Laura; de Crom, Tosca O E; Šímová, Zuzana; Ivanova, Mariia; Shahbaz, Muhammad Ali; et al. (Alzheimer's & dementia, 2024)
INTRODUCTION: Studies have correlated living close to major roads with Alzheimer's disease (AD) risk. However, the mechanisms responsible for this link remain unclear. METHODS: We exposed olfactory mucosa (OM) cells of healthy individuals and AD patients to diesel emissions (DE). Cytotoxicity of exposure was assessed, mRNA, miRNA expression, and DNA methylation analyses were performed. The discovered altered pathways were validated using data from the human population-based Rotterdam Study. RESULTS: DE exposure resulted in an almost four-fold higher response in AD OM cells, indicating increased susceptibility to DE effects. Methylation analysis detected different DNA methylation patterns, revealing new exposure targets. Findings were validated by analyzing data from the Rotterdam Study cohort and demonstrated a key role of nuclear factor erythroid 2-related factor 2 signaling in responses to air pollutants. DISCUSSION: This study identifies air pollution exposure biomarkers and pinpoints key pathways activated by exposure. The data suggest that AD individuals may face heightened risks due to impaired cellular defenses. HIGHLIGHTS: Healthy and AD olfactory cells respond differently to DE exposure. AD cells are highly susceptible to DE exposure. The NRF2 oxidative stress response is highly activated upon air pollution exposure. DE-exposed AD cells activate the unfolded protein response pathway. Key findings are also confirmed in a population-based study.
Keywords: Alzheimerova nemoc; Transcriptome; Gene Expression Profiling; čichová sliznice; senioři; Aged; Male; Air Pollutants; lidé; stanovení celkové genové exprese; lidé středního věku; Humans; mikro RNA; Middle Aged; výfukové emise vozidel; epigenomika; metylace DNA; Olfactory Mucosa; transkriptom; mužské pohlaví; Vehicle Emissions; DNA Methylation; MicroRNAs; látky znečišťující vzduch; NF-E2-Related Factor 2; ženské pohlaví; faktor 2 související s NF-E2; Alzheimer Disease; Female; Epigenomics